Effect of Leaflet-Based Nutrition Education on Nutritional Knowledge and Understanding of Obesity Risk among Older Adults at Posbindu Telukjambe, Karawang Regency - Muthmainah, Fitriyah Nafsiyah; J, Nurnashriana; Anggiruling, Dwikani Oklita; Elvandari, Milliyantri; Reisha, Granindya Naura Ayu (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Obesity among older adults is a growing public health concern associated with an increased risk of non-communicable diseases, particularly due to low nutritional knowledge and nutritional literacy as well as unhealthy lifestyle behaviors. This study aimed to determine the effect of nutrition education leaflets related to obesity on the level of nutritional knowledge and nutritional literacy among older adults at Posbindu Teluk Jambe, Karawang Regency. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The sample consisted of 31 older adults selected using total sampling. Data were collected using a structured questionnaire administered before and after the intervention. The intervention involved the distribution of nutrition education leaflets containing information on obesity, risk factors, health impacts, balanced nutrition, and physical activity recommendations. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test due to non-normal data distribution. The pre-test results showed a mean knowledge score of 3.81 ± 1.642 with a median of 4.00 and a score range of 1–7. After the intervention, the post-test mean score increased to 6.00 ± 1.065 with a median of 6.00 and a score range of 4–8. The Wilcoxon test showed Z = -3.771 with Asymp. Sig. (2-tailed) = 0.000 (p<0.05), indicating a significant difference between knowledge scores before and after the leaflet intervention. These findings demonstrate that nutrition education leaflets are effective in improving nutritional knowledge and supporting nutritional literacy among older adults. Key word: Older adults, obesity, nutritional literacy, nutrition education, leaflet.